"Dental Stem Cells": Awareness, knowledge, and attitude of dental professionals—A cross‐sectional study. (9th December 2019) - Goswami, Mridula; Kumar, Gyanendra; Sharma, Sadhna
Abstract: Aim: The present study was conducted with an aim to assess the awareness about existence of dental stem cells among dental professionals. Materials and Methods: A total sample size of 100 dental professionals in the age group of 22‐32 years, comprising of 28 interns, 46 postgraduate students, and 26 senior residents from various specialties was selected. A self‐administered, hand‐delivered, 10‐point questionnaire was used to assess the awareness, knowledge, and attitude of dental professionals towards dental stem cells. Results were documented and statistically analyzed using chi‐square test. Results: A total of 72% dental professionals were aware about dental stem cells with dental curriculum books being the main source of information. Note that 81% of positive respondents were aware about the different types and a total of 28% were aware about the procedure to procure dental stem cells. Only 33.3% of positive respondents were aware about existence of dental stem cell banks in India. Conclusion: A high level of awareness about dental stem cells and its applications was noted during the course of this study. A significant association of age and type of practice with awareness of dental stem cells and knowledge regarding their use in developing nondental tissues was observed. A positive attitude towards recommending dental stem cell banking was seen.